Predators of the green cassava mite in northeastern Brazil - Farias, Alba R.N.; Flechtmann, Carlos H.W.; Moraes, Gilberto J. de; McMurtry, James A. (Pesquisa Agropecuaria Brasileira, 2014)
This paper presents the following mites of the family Phytoseiidae as predators of Mononychellus tanajoa (Bonder) (Acari, Prostigmata, Tetranychidae) in northeastern Brazil: Typhlodromalus limonicus (Garman & McGregor), Typhlodromalus sp, Euseius flechtmanni Denmark & Muma, Euseius sibelius (DeLeon). Neoseiulus idaeus Denmark & Muma and Galendromus (Galendromus) annectens ( DeLeon). It also reports on the occurrence of Stethorus sp, probably darwini Bréthes (Coleoptera: Coccinellidae) and Oligota sp (Coleoptera: Staphylinidae) as predators of M. tanajoa in northeastern Brazil.